Penerapan Batuk Efektif Terhadap Peningkatan Saturasi Oksigen (SPO2) Pada TB Paru di Paru Center RSUD Ulin Banjarmasin: Application of Effective Cough on Increasing Oxygen Saturation (SPO2) on Patients with Tuberculosis at Paru Center RSUD Ulin Banjarmasin - Mahmudianti, Noor; Riduansyah, Muhammad; Irawan, Angga (LPPM STIKES Guna Bangsa, 2024)
Tuberculosis is an infectious disease caused by bacteria called Mycobacterium Tuberculosis which indicated by a few symptoms such as prolonged cough up to 2-3 weeks. However, a problem which usually occur is difficulty of excreting sputum and therefor, patients would experience difficulty of breathing which then resulting in decreasing oxygen saturation. After collecting secondary data of pressure ulcers at Paru Center RSUD Ulin Banjarmasin, it was found that there where 63 patients experiencing tuberculosis since April to June 2023. Identifying the application of effective cough on increasing oxygen saturation (SPO2) on patients with tuberculosis at RSUD Ulin Banjarmasin. This study used descriptive design. Sample on this study was selected using the total sampling technique. Data was collected using an observation sheet and the standard operating procedure of effective cough which was already provided at Paru Center. Before applicating the intervention, 2 patients had 95% of oxygen saturation, 5 patients with 96% oxygen saturation, 4 patients with 97% oxygen saturation, and 1 patient with 98% oxygen saturation. After the intervention was aplicated, 1 patient had 96% of oxygen saturation, 4 patients with 97% of oxygen saturation, 4 patients with 98% of oxygen saturation, and 3 patients had 99% of oxygen saturation. The lowest oxygen saturation before intervention was 95% and the highest oxygen saturation was 98%. However, after intervention, the lowest oxygen saturation was 96% and the highest oxygen saturation was 99%. It is expected for nurses to educate patients about effective cough according to the standard operating procedure.